Use of Expectation Disconfirmation Theory to Test Patient Satisfaction with Asynchronous Telemedicine for Diabetic Retinopathy Detection - Christina I. Serrano; Vishal Shah; Michael D. Abràmoff (International Journal of Telemedicine and Applications)
Objective. The purpose of the study is to extend research on patient satisfaction with telemedicine services by employing the theoretical framework of Expectation Disconfirmation Theory (EDT) for diabetic retinopathy screenings focusing on rural patients. Method. Adult subjects (n=220) with diabetes were recruited from a single family practice office in rural Iowa. Subjects completed a “pre” survey concerning their forward-looking perceptions of telemedicine prior to using telemedicine for detection of diabetic retinopathy and a “post” survey after they received recommendations from the distant ophthalmologists. Results. All hypotheses of the EDT model were supported. Patient satisfaction is influenced by both patients’ expectations (P<.001) and disconfirmation of expectations (P<.001), and patient satisfaction has a positive impact on patient preference for telemedicine services (P<.001). Overall, patients who received telemedicine services were highly satisfied with telemedicine and developed a favorable disposition towards telemedicine services. Conclusions. The EDT model is a viable framework to study patient satisfaction of telemedicine services. While previous feasibility studies have shown that telemedicine for diabetic retinopathy screenings yields diagnostic efficacy, this study applies a theoretical framework to demonstrate the viability of telemedicine for diabetic retinopathy screenings in rural areas.